2007
DOI: 10.1002/ibd.20238
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of long-term enteral nutrition on clinical and endoscopic disease activities and mucosal cytokines during remission in patients with Crohnʼs disease: A prospective study

Abstract: Long-term enteral nutrition in patients with quiescent CD has a clear suppressive effect on clinical and endoscopic disease activities and the mucosal inflammatory cytokine levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
123
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 38 publications
2
123
0
3
Order By: Relevance
“…The full text of the remaining 36 records was examined, of which 12 (representing eight unique studies) were included in the review. 28,[50][51][52][53][54][55][56][57][58][59][60] Of the eight included studies, one RCT [52][53][54] and one nRCT 28,59,60 were represented in multiple publications. Throughout this review, these two studies will be cited according to their corresponding original publications.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…The full text of the remaining 36 records was examined, of which 12 (representing eight unique studies) were included in the review. 28,[50][51][52][53][54][55][56][57][58][59][60] Of the eight included studies, one RCT [52][53][54] and one nRCT 28,59,60 were represented in multiple publications. Throughout this review, these two studies will be cited according to their corresponding original publications.…”
Section: Literature Searchmentioning
confidence: 99%
“…The study and participant characteristics of the five included nRCTs 28,51,[56][57][58] are summarised in Table 2. Of five studies, four were conducted in Japan 28,51,57,58 and one in the UK.…”
Section: Non-randomised Controlled Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of EN, only one study has shown that during the fol-low-up period, CD patients in whom remission was induced by parenteral nutrition presented lower recurrence rates if they were kept on EN compared to those who were not (56). Indeed, available evidence suggests that supplementary EN may be effective as an alternative or adjunct therapy for maintaining remission in adult CD patients (57) (62). However, in order to confirm these findings, more extensive well-powered studies are needed, especially trials comparing EN with azathioprine and infliximab, which are known to be effective in maintaining remission in CD patients.…”
Section: Nutritional Maintenance Therapymentioning
confidence: 99%
“…Enteral nutrition (EN), administered orally or via tube feeds, reduces inflammatory markers [8] and mucosal cytokines [9], while improving gut permeability [10] and modifying gut flora [11]. In one non-randomized trial, the relapse rate at 1 year was 25 % in the EN group versus 65 % in the non-EN group, with reported significant improvement in average endoscopy scores, with decreased mucosal concentrations of IL-1b, -6, and TNF [9]. In a meta-analysis of seven studies, EN with elemental, semi-elemental or polymeric diets orally or via tube feeds had higher clinical remission rates compared to groups ingesting ordinary foods [12].…”
mentioning
confidence: 99%